Antibacterial properties of ethanolic extracts from Melochia pyramidata L. - Carrillo, María Fernanda; Ortiz-Rojas, Luz Yineth; Chaves-Bedoya, Giovanni (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2024)
This study investigates the antibacterial properties of ethanolic extracts from the weed Melochia pyramidata L. Through gas chromatography-mass spectrometry (GC-MS) analysis, several compounds were identified, including pyranones, phenolic compounds, terpenes, coumarin, aryl-tetrahydrofurans, and phenylpropanoids. Among the most abundant compounds were 3,5-dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one and palmitic acid. Although several known metabolites were identified, the main focus was on evaluating the antibacterial capacity of the complete extract. The study's findings indicate that the ethanolic extract exhibits substantial inhibition against various bacteria. Specifically, Gram-positive S. aureus showed the greatest sensitivity to the extract, with an average inhibition zone of 13.12 mm, followed by E. coli with an average inhibition of 10.95 mm. These findings suggest that the M. pyramidata extract could be a promising source for the development of antimicrobial agents. However, it is emphasized that the tests were conducted in vitro, and further research is needed to confirm the efficacy of the extract in clinical in vivo applications. This study highlights the importance of evaluating underexplored natural resources like weeds in the search for antimicrobial solutions and contributes to the understanding of the potential of M. pyramidata in antibacterial research.